Carbon Storage in Mountain Land Use Systems in Northern Thailand - Narit Yimyam (2018)
© 2016. Yimyam et al. Conversion of forested land for agriculture has obvious detrimental effects on its ecological functions, but these effects are not uniform. Mountain land use systems are diverse, encompassing managed forests and cultivated land. This study examined land use systems in 3 mountain villages in northern Thailand with different patterns of cultivation and evaluated the amount of carbon they have accumulated. Land use and management by individual farmers and communities were determined by interviews, field verification, and mapping. Biomass carbon in trees was determined nondestructively, and carbon in ground cover, litter, and soil organic matter was determined by chemical analysis of replicated samples. The 3 villages, with access to land ranging from 1.3 to 6.3 ha per capita, managed largely pristine headwater forests for security of water supply and made a living from crop production supplemented by harvests of timber, firewood, and other forest products from managed community forests. Cultivated land varied in composition and management among the villages, from shifting cultivation with fallow periods of different lengths to permanent cultivation of food and commercial crops. Per capita carbon storage in the villages well exceeded average per capita carbon dioxide emissions in Thailand, with most of the carbon stored in the forests. This has important implications for programs that offer incentives to mountain villages to maintain or enhance their carbon storage, such as the United Nations' REDD (Reducing Emissions from Deforestation and Forest Degradation) program.